Analisis Faktor yang Mempengaruhi Implementasi Standar Keselamatan Pasien - Marlina, Nina; Budiman, Budiman; Oyoh, Oyoh; Mulyati, Mulyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the factors that can influence the implementation of patient safety standards. The method used is correlational analysis with a cross-sectional approach. The results of the study indicate that there is a significant partial effect of gender on the implementation of patient safety standards p-value of 0.005; there is a significant partial effect of education on the implementation of patient safety standards p-value of 0.011, meaning that there is a significant partial effect of length of service on the implementation of patient safety standards p value 0.037; there is a significant partial effect of awareness on the implementation of patient safety standards p value 0.001; compliance has a partial considerable impact on the implementation of patient safety standards p value 0.001. In conclusion, awareness is the dominant factor influencing the implementation of patient safety standards. Keywords: Nurse Compliance, Nursing Services, Patient Safety Standards